Mobility-based performance comparison of MBQA-OLSRv2 and MBMA-OLSRv2 routing protocols - Jabbar, Waheb A. (IEEE Xplore, 2020)
This paper investigates the performance of proposed multipath routing protocols for energy-efficient and QoS awareness pending on nodes mobility in MANETs. In particular, multipath battery and queue aware routing (MBQA-OLSRv2) and ultipath battery and mobility aware routing (MBMA-OLSRv2) were valuated. EXata network simulator is used to conducts xtensive simulations to compare various energy and QoS- elated metrics for the proposed schemes. Simulation results prove that the MBMA-OLSRv2 scheme outperformed MBQA-OLSRv2 routing scheme in terms of several metrics such as; throughput, energy cost per packet, total packets dropped, consumed energy and delay especially in high mobility scenarios.